Penguin puzzle - Stamper, Judith Bauer; Enik, Ted (2001)
"Ms. Frizzle whisks her students away on a 'cool' trip to Antarctica, where they learn all about the South Pole and come face to face with playful penguins and colossal icebergs. When the kids are magically changed into real penguins, they need Ms. Frizzle's help to solve their penguin puzzle"--Provided by publisher.
"Based on The Magic School Bus books written by Joanna Cole and illustrated by Bruce Degen."--T.p. verso.
Keywords: Penguins -- Juvenile literature; South Pole -- Juvenile literature; Antarctica -- Juvenile literature